Above-ground biomass and carbon stock estimation of Harumanis using artificial neural network and random forest / Siti Noor Syazwani Zakaria, Nurul Ain Mohd Zaki and Farrah Melissa Muharam - Zakaria, Siti Noor Syazwani; Mohd Zaki, Nurul Ain; Muharam, Farrah Melissa (College of Built Environment, 2023)
The artificial neural network and random forest are the popular machine learning algorithms to estimate above-ground biomass and carbon stock. This algorithms will be used to estimate the carbon stock for Harumanis.